Social Entrepreneurial Intentions: An Empirical Study at Ponpes Darul Qur’am - Hartati, Anis Siti; Warsiki, A.Y.N; Kusmantini, Titik; Diantoro, Aris Kuumo (PINISI Discretion Review, 2022)
Social entrepreneurship combines social intentions with economic intentions and has become a major driving force for business transformation. Social entrepreneurship plays an important role in growing an entrepreneurial spirit. This study explores the social entrepreneurial intentions of Islamic boarding school of Darul Qur'an Wonosari students. This study examines moral obligation, empathy, self-efficacy and social support as the main determinants of social entrepreneurial intentions in Islamic boarding schools. This study uses a quantitative approach, through surveys to explore the effect of antecedents on social entrepreneurial intentions from student samples who got responsibilities to manage Islamic boarding schools and their business units. By using the statistical method of partial least squares structural equation modeling (PLS-SEM) for data analysis.